Enantioselective Michael Addition of Cyclic β-Diones to α,β-Unsaturated Enones Catalyzed by Quinine-Based Organocatalysts - Wang, Qingqing (Molecules, 2017)
An enantioselective (52–98% ee) Michael addition between cyclic β-diones and α,β-unsaturated enones was established in the presence of quinine-based primary amine or squaramide. A variety of cinnamones were smoothly converted into the desired 3,4-dihydropyrans in moderate to high yields (63–99%). Chalcones were also suitable acceptors and gave rise to the expected adducts in satisfactory yields (31–99%). The resulting adducts readily underwent further modification to form fused 4H-pyran or 2,3-dihydrofuran.